Sudan Strategy Support Program (SSSP): Background and research output - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The Sudan Strategy Support Program (SSSP), one of the country programs of the International Food Policy Research Institute (IFPRI), commenced operations in May 2022 from the premises of the Arab Organization for Agricultural Development, its official host institution in Sudan. Established with funding from USAID, the United States Agency for International Development, the program has also formed partnerships or received support from a number of prominent organizations, including the CGIAR Initiative on Fragility, Conflict, and Migration, the CGIAR Initiative on NEXUS Gains, the United Nations Development Programme, the World Bank, the World Food Programme, the International Center for Agricultural Research in the Dry Areas, and the International Maize and Wheat Improvement Center (CIMMYT).